Bortezomib, lenalidomide, and dexamethasone with or without elotuzumab in patients with untreated, high-risk multiple myeloma (SWOG-1211): primary analysis of a randomised, phase 2 trial. Issue 1 (January 2021) - Usmani, Saad Z; Hoering, Antje; Ailawadhi, Sikander; Sexton, Rachael; Lipe, Brea; Hita, Sandi Fredette; Valent, Jason; Rosenzweig, Michael; Zonder, Jeffrey A; Dhodapkar, Madhav; Callander, Natalie; Zimmerman, Todd; et al.
Summary: Background: The introduction of immunomodulatory agents, proteasome inhibitors, and autologous haematopoietic stem-cell transplantation has improved outcomes for patients with multiple myeloma, but patients with high-risk multiple myeloma have a poor long-term prognosis. We aimed to address optimal treatment for these patients. Methods: SWOG-1211 is a randomised phase 2 trial comparing eight cycles of lenalidomide (25 mg orally on days 1–14 every 21 days), bortezomib (1·3 mg/m 2 subcutaneously on days 1, 4, 8, and 11 every 21 days), and dexamethasone (20 mg orally on days 1, 2, 4, 5, 8, 9, 11, and 12 every 21 days; RVd) induction followed by dose-attenuated RVd maintenance (bortezomib 1 mg/m 2 subcutaneously on days 1, 8, and 15; lenalidomide 15 mg orally on days 1–21; dexamethasone 12 mg orally on days 1, 18, and 15 every 28 days) until disease progression with or without elotuzumab (10 mg/kg intravenously on days 1, 8, and 15 for cycles 1–2, on days 1 and 11 for cycles 3–8, and on days 1 and 15 during maintenance). Patients were randomly assigned (1:1) to either RVd or RVd-elotuzumab. High-risk multiple myeloma was defined by one of the following: gene expression profiling high risk (GEP hi ), t(14;16), t(14;20), del(17p) or amp1q21, primary plasma cell leukaemia and elevated serum lactate dehydrogenase (two times the upper limit of normal or more). The primary endpoint was progression-free survival, and all analyses were done on intention-to-treat basis among eligible patients who were evaluable for response. This study is registered with ClinicalTrials.gov, NCT01668719 . Findings: 100 (RVd n=52, RVd-elotuzumab n=48) patients were enrolled between Oct 27, 2013, and May 15, 2016, across 26 cooperative group institutions in the USA. Median age was 64 years (IQR 57–70, range 36–85). 74 (75%) of 99 had International Staging System stage II or stage III disease, 47 (47%) of 99 had amp1q21, 37 (37%) of 100 had del17p, 11 (11%) of 100 had t(14;16), eight (9%) of 90 were GEP hi, seven (7%) of 100 had primary plasma cell leukaemia, five (5%) of 100 had t(14;20), four (4%) of 100 had elevated serum lactate dehydrogenase, and 17 (17%) had two or more features. With a median follow-up of 53 months (IQR 46–59), no difference in median progression-free survival was observed (RVd 33·64 months [95% CI 19·55–not reached], RVd-elotuzumab 31·47 months [18·56–53·98]; hazard ratio 0·968 [80% CI 0·697–1·344]; one-sided p=0·45]. 37 (71%) of 52 patients in the RVd group and 37 (77%) of 48 in the RVd-elotuzumab group had grade 3 or worse adverse events. No significant differences in the safety profile were observed, although some notable results included grade 3–5 infections (four [8%] of 52 in the RVd group, eight [17%] of 48 in the RVd-elotuzumab group), sensory neuropathy (four [8%] of 52 in the RVd group, six [13%] of 48 in the RVd-elotuzumab group), and motor neuropathy (one [2%] of 52 in the RVd group, four [8%] of 48 in the RVd-elotuzumab group). There were no treatment-related deaths in the RVd group and one death in the RVd-elotuzumab group for which study treatment was listed as possibly contributing by the investigator. Interpretation: In the first randomised study of high-risk multiple myeloma reported to date, the addition of elotuzumab to RVd induction and maintenance did not improve patient outcomes. However, progression-free survival in both study groups exceeded the original statistical assumptions and supports the role for continuous proteasome inhibitors and immunomodulatory drug combination maintenance therapy for this patient population. Funding: National Institutes of Health, National Cancer Institute, Bristol Myers Squibb, Celgene, Leukemia and Lymphoma Society.